Biomass and nutritional evaluation of German grass (Echinochloa polystachya) cultivated on floating bed (Bangladesh Journal of Animal Science, 2018)
German and Napier grasses were cultivated on floating agricultural bed at the valley of Sylhet Agricultural University (SAU) to find out a suitable fodder for floating bed fodder cultivation. Later, German grass was cultivated on five floating beds at Hemupara of Jaintapur, Sylhet and also produced at land of SAU campus. German grass samples from both floating beds and land, as well as local Bermuda grass from Hemupara were evaluated for assessment of biomass production, proximate and fiber composition. There was no significant difference in length and production of German grass cultivated on floating bed and land cultivation. German grass production cost on floating bed was 2.3 Tk/kg. German grass from floating bed contained more ether extract, Ash, Neutral detergent fiber and cellulose than that from land cultivation. DM, Ash, CP, EE, CF and NFE of German grass on floating beds at Hemupara were 199.7g/kg, 20.1g/kg, 57.2g/kg, 37.2g/kg, 411.8gm/kg and 273.9g/kg respectively. The fiber components of German grass on floating beds were NDF (696.4g/kg), ADF (452.2g/kg), ADL (100.1g/kg), cellulose (244.1g/kg) and hemicellulose (352.1g/kg). German grass can be considered as a suitable fodder for floating bed fodder cultivation when there is long term water logging as an alternative fodder production practice in Bangladesh.Bang. J. Anim. Sci. 2017. 46 (4): 249-257